SCAFOLDING AS A TOOL TO DEVELOP PRE SERVICE TEACHERS’ SCIENTIFIC THINKING ABILITY - Rahman, Taufik (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Scaffolding is a necessary process to achieve learners potential ability. This study depicts the importance of scaffolding in achieving scientific thinking ability. Subjects were 24 pre-service teachers enrolled in Teacher Professional Development Program. Results showed that pre-service biology teachers’ average scientific thinking ability was categorized as low and scaffolding was greatly needed to serve as a tool to enhance pre-service biology teachers’ scientific ability. Scaffolding scheme for Teacher Professional Development Program is proposed.